2006
DOI: 10.1063/1.2206177
|View full text |Cite
|
Sign up to set email alerts
|

The methyl C–H blueshift in N,N-dimethylformamide-water mixtures probed by two-dimensional Fourier-transform infrared spectroscopy

Abstract: Two-dimensional correlation spectroscopy was used to study the composition-dependent spectral variations of the CH-stretching bands of N,N-dimethylformamide (DMF)-water mixtures with X(DMF) ranging from 0.98 to 0.60. By a detailed correlation analysis of the spectral changes of the CH- and OH-stretching bands, it is found that the intensities of the CH and OH bands change in different ways when the water content is increased. It is also found that two different regions of the water content can be distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
3
20
0
2
Order By: Relevance
“…The broader band width of C=O stretch in the PCA compared with that of CA also supports the enhanced H-bonding characteristics of the polymer. 52 The peak at 1356 cm -1 in the CA (monomeric COOH) is due to the in-plane OH deformation of COOH, and it disappears when the carboxylic acid is esterified with H 2 SO 4 . It is important to notice that the OH deformation peak in the PCA does not appear as well at this region.…”
Section: Resultsmentioning
confidence: 99%
“…The broader band width of C=O stretch in the PCA compared with that of CA also supports the enhanced H-bonding characteristics of the polymer. 52 The peak at 1356 cm -1 in the CA (monomeric COOH) is due to the in-plane OH deformation of COOH, and it disappears when the carboxylic acid is esterified with H 2 SO 4 . It is important to notice that the OH deformation peak in the PCA does not appear as well at this region.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of these works have been limited to small model systems60–63 whose pertinence to proteins is questionable. More recent work extended this analysis to amides64–66, where it was found that the donor CH bond undergoes fairly large blue shifts when engaged in a H‐bond, as well as a marked weakening of the CH stretching band. In clear contrast, when this same CH is peripheral to a H‐bond that occurs elsewhere in the amide, the shifts might be in either direction but would be of considerably smaller magnitude.…”
Section: Introductionmentioning
confidence: 90%
“…离子液体(ILs)具有挥发性低、溶解能力强、结 构与功能可设计等特点, 在化学反应 [1,2] 、酸性气体 吸收 [3~7] 、电化学 [8] 和材料合成 [9] 谱学手段具有灵敏度高、样品量少、测量方便 快捷和可用于探测分子水平上的微观环境等特点, 近年来已经在缔合溶液微观结构、相互作用和热力 学性质研究方面发挥着越来越重要的作用 [10,11] . 目 前, 研究缔合溶液体系相互作用和热力学性质常用 的谱学手段包括核磁共振波谱 [12,13] 、红外光谱 [14,15] 和拉曼光谱 [16] 等. 例如, Xu 等 [12] 通过内标法测定了 醇/烃体系全浓度范围内的 1 H NMR 化学位移, 并采 用局部组成模型关联了体系的 1 H NMR 化学位移随 浓度的变化, 利用获得的能量参数直接预测了上述 体系的汽液平衡数据, 建立了醇/烃体系 1 H NMR 化 学位移和汽液平衡之间的定量关系.…”
Section: 引言unclassified